2015
DOI: 10.3390/educsci5040281
|View full text |Cite
|
Sign up to set email alerts
|

Teenagers’ Expectations of Applying to University: How do they Change?

Abstract: We show how young people's expectations about application to university change during the teenage years, drawing on the Longitudinal Study of Young People in England (LSYPE). We reveal the pattern of change by family background, prior attainment at the end of primary school (measured by Key Stage 2 tests) and, critically, the combination of the two. We document the relationship between expectations about university application and the decision on whether to stay on in full-time education at 16. We point to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 9 publications
0
32
0
1
Order By: Relevance
“…However, Morgan (1998) argues that 'educational expectations are not "flights of fancy" or "vague preferences" [but rather,] because they can be explained by a reasonable theory of rational behavior, should be considered rational' (p. 157) and hence, presumably, informative. Certainly, previous work has shown a correlation between educational expectations and later outcomes in several developed countries around the world (Anders & Micklewright, 2015;Chowdry et al, 2011;Khoo & Ainley, 2005;Reynolds & Pemberton, 2001). Why do these associations exist?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Morgan (1998) argues that 'educational expectations are not "flights of fancy" or "vague preferences" [but rather,] because they can be explained by a reasonable theory of rational behavior, should be considered rational' (p. 157) and hence, presumably, informative. Certainly, previous work has shown a correlation between educational expectations and later outcomes in several developed countries around the world (Anders & Micklewright, 2015;Chowdry et al, 2011;Khoo & Ainley, 2005;Reynolds & Pemberton, 2001). Why do these associations exist?…”
Section: Introductionmentioning
confidence: 99%
“…There exists a previous literature on the formation and correlates of young people's educational expectations and aspirations (Anders & Micklewright, 2015;Baker et al, 2014;Chowdry, Crawford, & Goodman, 2010;Rampino & Taylor, 2013). Previous work has always found a role for SES.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same dataset, Anders and Micklewright (2015) have been able to highlight the importance of parents' education on young people's expectations, particularly if they had been to university themselves. But importantly, they showed that levels of attainment at the end of primary school education seemed to be more important in shaping expectations than having an advantaged family background.…”
Section: The Determinants Of Participation Into Higher Educationmentioning
confidence: 98%
“…As noted earlier, attributing causation to a cluster variable is problematic. As Anders and Micklewright (2015) pointed out, these school "effects" could reflect a number of school-level factors, including peer influences and family attributes that are associated with a school's intake. Nevertheless, the use of multilevel models allows us to estimate the size of effects at the school level, from which further consideration of the causal relationships is now possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation